In Vivo Anti-Leukemia, Quantum Chemical Calculations and ADMET Investigations of Some Quaternary and Isothiouronium Surfactants - Ahmed A. El-Henawy; Manal M. Khowdiary; Abdelfattah B. Badawi; Hussein M. Soliman (MDPI AG, 2013)
Anti-leukemia screening of previously prepared isothiouronium and quaternary salts was performed, and some salts exhibited promising activity as anticancer agents. Quantum chemical calculations were utilized to explore the electronic structure and stability of these compounds. Computational studies have been carried out at the PM3 semiempirical molecular orbitals level, to establish the HOMO-LUMO, IP and ESP mapping of these compounds. The ADMET properties were also studied to gain a clear view of the potential oral bioavailability of these compounds. The surface properties calculated included critical micelle concentration (CMC), maximum surface excess (Γmax), minimum surface area (Amin), free energy of micellization (ΔGomic) and adsorption (ΔGoads).